Aimless Lives: Amateur Aesthetics, Mexican Contemporary Art, and Sarah Minter's Alma Punk. Issue 1 (2nd January 2020) - Ramos, Iván A
Abstract: This article makes use of the notion of amateurism to reframe our understandings of Mexican contemporary art of the late 1980s and early 1990s. I look specifically at Sarah Minter's 1991 feature length video piece Alma Punk to suggest that its deployment of an aesthetics of amateurism indexes the oft-forgotten intersection between punk subcultures and the contemporary art scene of the period. Countering dominant discourses in art historical discussions that subsume Mexican contemporary art to macro-political and economic developments, I situate Alma Punk as an object that allows us to recognise the marginal spaces from which this art emerged. I locate amateurism in this article in close relation to Manny Farber's idea of 'termite art', an aesthetic mode that favors the reach of minor gestures against the will toward mastery found in 'white elephant art'. Thus, Minter's work chooses amateurism as an aesthetic mode that approximates the everyday experiences of her marginal subjects.